PENGARUH MODEL KOOPERATIF TIPE STAD TERHADAP AKTIVITAS DAN PENGUASAAN MATERI SISWA - Sasmita Erzana; Tri Jalmo; Rini Rita T Marpaung (Universitas Lampung, 2013)
The observation at X class SMA N 3 Kotabumi, known that mastery of material by students are still low. An alternative models to solve that is STAD. The objectives of this research were to know the influence of STAD model in improving student learning activities and mastery of material. The research is a quasi experiment with design pretest-posttest nonequivalent. The sample was students at X7 and X6 which chosen with purposive sampling. The quantitative data was gattered from value pretest, posttest, and N-gain score which was analyzed statistic using t-test. The qualitative data in form of description activities and questionnaire of students response of using STAD models. The result of student learning activities are in average good criteria. In the aspect worth asking (86.3%), answer questions (76.9%) and expression (87.7%). Mastery of the material has increased, with N-gain average (0,73). Questionnaire showed that all group leaders felt aid group members in discussions and members find it easier to understand the material and with the help of leaders in discussions. Thus, that the application of the model STAD effect on the activities and significant effect mastery of the material. Keywords: biodiversity, learning activities, mastery of the material, and STAD model.